Marine Cyanobacteria: A Rich Source of Structurally Unique Anti-Infectives for Drug Development - Lik Tong Tan; Nurul Farhana Salleh (Molecules)
Marine cyanobacteria represent a promising yet underexplored source of novel natural products with potent biological activities. Historically, the focus has been on isolating cytotoxic compounds from marine cyanobacteria, but a substantial number of these photosynthetic microorganisms also produce diverse specialized molecules with significant anti-infective properties. Given the global pressing need for new anti-infective lead compounds, this review provides a concise yet comprehensive overview of the current knowledge on anti-infective secondary metabolites derived from marine cyanobacteria. A majority of these molecules were isolated from free-living filamentous cyanobacteria, while several examples were derived from marine cyanobacterial symbionts. In addition, SAR studies and potent synthetic analogs based on selected molecules will be featured. With more than 200 molecules, this review presents their antibacterial, antifungal, antiviral, antiprotozoal, and molluscicidal activities, with the chemical and biological information covered in the literature up to September 2024.